The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3233/cbm-140389
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs11614913 polymorphism in miR-196a2 and colorectal cancer risk: A meta-analysis

Abstract: These findings supported that miR-196a2 rs11614913 polymorphism may contribute to the susceptibility of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(77 reference statements)
0
6
0
Order By: Relevance
“… 173 Ren et al 174 reported the association of rs11614913 with lung cancer in a meta-analysis with 5 studies, which is consistent with our findings. Other meta-analyses with individual cancer susceptibility also produced conflicting outcomes, such as in breast cancer, 175 gastric cancer, 176 , 177 colorectal cancer, 178 , 179 esophageal cancer, 180 and prostate cancer. 181 …”
Section: Discussionmentioning
confidence: 99%
“… 173 Ren et al 174 reported the association of rs11614913 with lung cancer in a meta-analysis with 5 studies, which is consistent with our findings. Other meta-analyses with individual cancer susceptibility also produced conflicting outcomes, such as in breast cancer, 175 gastric cancer, 176 , 177 colorectal cancer, 178 , 179 esophageal cancer, 180 and prostate cancer. 181 …”
Section: Discussionmentioning
confidence: 99%
“…Variation in microRNA expression has also been implicated in CRC carcinogenesis [6,9,11] with many conflicting reports regarding the association of miR-196A2 C>T polymorphism with the risk of CRC in humans [11,30,32] . Multiple genetic alterations in tumor suppressor genes like Deleted in Colorectal Cancer (DCC) gene have also been found to be associated with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhan et al, [47] also confirmed an enhanced expression of miR-196A2 in colorectal cancer tissues of patients with the CC or CT genotypes as compared to TT genotype. The discrepancy in results between studies regarding the probable significance of miR196A2 rs 11614913 in CRC may be attributable to some factors: Such as sample size with a consequent reduced statistical power to assess the association between the polymorphisms and susceptibility to CRC; histological patterns or types of CRC; different ethnicity and genetic variants or different molecular pathological mechanisms that contribute differently to cancer [32,41] . Therefore, further studies with larger sample size and incorporation of gene-gene and gene-environment interactions are warranted to confirm these findings [41,48] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, some studies have revealed that miRNA expression profiles and some specific miRNAs were associated with the risk of CCRCC [7][8][9][10][11][12][13][14][15][16]. Considerable studies have specified that single-nucleotide polymorphisms (SNPs) in miRNA genes could alter miRNA processing and expression and contribute to cancer risk [17][18][19][20]. However, limited information was available for CCRCC.…”
Section: Introductionmentioning
confidence: 99%